Development of Students’ Science Worksheets Based on Liveworksheet As Alternative Learning Resources for Junior High School Students - Yusro, Andista Candra; Safitri, Wulan; Ngabdiningsih, Sestu Wilujeng; Taqwim, Mohamad Ahsanul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Liveworksheet-based science student worksheets on the substance pressure topic are a form of science worksheet development and can be accessed on the Liveworksheet website. This study aims to develop science worksheets based on a